49.4: Long Viewing Distance and Large Depth of Field Augmented Reality (AR) 3D Display Based on MEMS Laser Projection Array. (26th August 2021) - Meng, Yang; Lyu, Yan; Zhang, Nan; Li, Ruiyang; Yu, Zhongyuan; Chen, Laurence Lujun; Zhang, Xinran; Huang, Tianqi; Ma, Longfei; Liao, Hongen
Abstract : The light collimation performance of each imaging unit in integral photography determines the viewing distance and depth of the field of the stereoscopic scene. MEMS laser projector has a good light collimation effect. Our work is to implement MEMS array extension through the subtle design of light paths. The single‐line MEMS scanning array and the multi‐mirror array are finely coordinated. Projection array realizes stereo display by transforming spatial pixels into angle information. The 3D light field is rendered using the space‐time multiplexing technology of MEMS laser scan projection. On this basis, we try to replace the multi‐mirror array with a semi‐transmission and semi‐reflection mirror array to achieve augmented reality. The mirror array can balance the number of views and pixels. The depth information of the real object is obtained using the structured light scanning technology of the depth camera. The calibration, registration, accurate fusion, and in‐situ superposition of the 3D reconstruction scene and the natural scene are realized.